NOVEL intronic CAPN3 Roma mutation alters splicing causing RNA mediated decay. Issue 11 (14th October 2019) - Mavillard, Fabiola; Madruga‐Garrido, Marcos; Rivas, Eloy; Servián‐Morilla, Emilia; Ávila‐Polo, Rainiero; Marcos, Irene; Morón, Francisco J.; Paradas, Carmen; Cabrera‐Serrano, Macarena
Abstract: CAPN3 mutations cause a limb girdle muscular dystrophy. Functional characterization of novel mutations facilitates diagnosis of future cases. We have identified a novel (c.1992 + 2T>G) CAPN3 mutation that disrupts the donor splice site of intron 17 splicing out exon 17, with mRNA levels severely reduced or undetectable. The mutation induces a strong change in the 3D structure of the mRNA which supports no‐go mRNA decay as the probable mechanism for RNA degradation. The mutation was identified in two unrelated Roma individuals showing a common ancestral origin and founder effect. This is the first Roma CAPN3 mutation to be reported.